Dilatancy of cement slurries with chemical admixtures - Skripkiūnas, Gintautas; Daukšys, Mindaugas (Journal of Civil Engineering and Management, 2004)
The results of experimental investigation of plasticising, air‐entraining and viscosity‐modifying admixtures with different chemical composition influence on rheological properties and dilatancy of cement slurries are presented in the article. Rheological properties of cement slurries were tested by a rotation viscometer with coaxial cylinder, at different gradients of velocity. Dilatancy of cement slurries was determined by the distortion of the rheological curve and index of dilatancy D was calculated according to proposed methods. The results of investigation show that the properties of liquid disperse medium of structural system influence slightly the dilatancy of cement slurries. Plasticising admixtures with a different chemical composition slightly increases but air‐entraining and viscosity‐modifying admixtures slightly reduces the dilatancy of cement slurries.First Published Online: 14 Oct 2010